Twenty Years of Neonatal Screening for Sickle Cell Disease in Brazil: The Challenges of a Continental Country with High Genetic Heterogeneity - Santos, Helena Pimentel Dos; Domingos, Claudia Regina Bonini [UNESP]; Castro, Simone Martins De (Latin American Society Inborn Errors and Neonatal Screening (SLEIMPN); Instituto Genética para Todos (IGPT), 2021)
Sickle cell disease (SCD) is the most common inherited hematological disease worldwide. The benefits of diagnosis and early intervention have led to the wide dissemination of public health programs worldwide. Through neonatal screening programs, it is possible to reduce morbidity and mortality in the first 5 years of life. The prophylactic use of penicillin, the anti-pneumococcal vaccine and other intensive care, increase the survival and quality of life of people with SCD. The aim of this study is to present the 20-year history of screening for hemoglobinopathies in Brazil and its challenges. From 2001 to 2019, an average of 2,400,000 children were screened per year nationwide, with the coverage being of 82,16%. The screening of 54,9% of newborns is collected up to their 5th day of life. The prevalence of SCD was 1:2,263 newborns; therefore, it was the second most-common disease detected by the program of Brazil, being only after hypothyroidism (1/2,175 live births). The healthcare system should provide the necessary infrastructure to confirm the diagnosis of newborns and to provide appropriate counseling and treatment. The early diagnosis and treatment, as well as the follow-up with a multidisciplinary team, are fundamental to the survival rate and the quality of life of patients.
Keywords: Newborn screening; Sickle Cell Disorder; Brazil; National Program